Respuesta del pimiento capsicum annuum variedad yolo wonder a la formulación de abonos orgánicos en la granja Sta. Inés - González Romero, Darwin Alberto (2011)
The following investigation was made at Experimental Farm of the Science Agricultural to University Technical of Machala located at km 5,5 Paquisha Route, beloging of Parish El Cambio, Canto Machala, El Oro province, Ecuador, where was tried differents organic fertilizer mix in cultivate. It is a vegetable pepper of high consume for the community. The objectives that presented to this investigation were: 1. Establish the answer of pepper to the organic fertilization. 2. Identify the organic fertilizer with the best results in production. 3. Make a economic analysis of results. The variety chosen to this analysis was Yolo Wonder because it is the most adapted variety in this place. It was proof defferents mixes of organics fertilizer composed for the following way: T1 = Compost 50 % + Guano de Isla 25 % + Gallinaza 25 %; T2 = Compost 50 % + Guano de Chivo 25 % + Gallinaza 25 %; T3 = Compost 75 % + Guano de Isla 20 % + Sulfato de Potasio 5 %; T4 = Compost 75 % + Guano de Chivo 20 % + Sulpomag 5 %; T5 = Ecoabonaza 95 % + Zeolita 5 %; T6 Absolute Witness. The experimental design chosen for this trial was the Block by Chance; in addition, with six treatments showed a high significative in all variables, but it's not between in repetitions. The evaluate factors were: height to 45, 90 days and to harvest; fruit's length; fruit's diameter; numbers of fruit for each plant; weight averaged of fruit. Performance for plot and cost of production and profitability. The better performances were the obtained fruit in the plot that was cultivated in of fertilizer mixes T2 equivalent to 29,7 kg where for consequently the contribution of phosphorus obtained for the Gallinaza the fruits were biggest and more heavy than the rest of the plot. In conclusion, the mix T2 is the best than the others treatments, but it's not appealing vs the obtained in conventional crop.